Strengthening of Nurul Ilmi Mosque with Concrete Jacketing - Fauzan Fauzan; Febrin Anas Ismail; Siska Apriwelni; Imelia Faradiza; Zev Al Jauhari (Universitas Lampung, 2016)
Abstract—Nurul Ilmi moesque is one of building for worship located in University of Andalas. In 2008 the new building of mosques was designed using previous indonesian seismic code, SNI 1726: 2002. The right side of the new mosque was constructied in 2009. Due to the limitation of the budget, the construction of the left side of the mosque was continued on 2014. However, a new indonesian seismic code SNI 03-1726-2012 was established and the designed mosque should be revised based on the new indonesian seismic code. Since the right side of the mosque was designed by using the old seismic code (SNI 1726: 2002), so it is necessary to evaluate the strength of the structure by using the seismic code (SNI 03-1726-2012). Based on the analysis results, it was found that the right side of the building structure is not strong enough to resist the combination loads acting on the structure, especially the earthquake load. Therefore, it is necessary to strengthening (retrofitting) the right side of the building structure before connecting with the left side of the building. In this study, the concrete jacketing method was used to the retrofit the column structure. The results show that the jacketing method is effective to increase the capacity of the column and reduce internal forces and displacements that occur in the structure of the mosque, so the structure can resist the working loadsKeywords—column, concrete jacketing, earthquake, displacement, strengthening.